O paradoxo das identidades indígenas no Poder Judiciário: o caso Raposa Serra do Sol, o Supremo Tribunal Federal e o reconhecimento da identidade étnica dos indígenas: necessidade de repensar o status jurídico efetivo dos indígenas no Brasil - Daize Fernanda Wagner (2017)
This research has the aim to discuss the ethnic identity of the indigenous in Brazil and the materialization of their constitutional rights starting from the promulgation of the Federal Constitution of Brazil in 1988 (CR/88). The understanding on the ethnic identity in the Social sciences has changed significantly since 1970s, highlighting the studies developed by the anthropologist Fredrik Barth on the ethnic groups and their borders. Breaking with the cultural conception as core for the explanation of existence and maintenance of ethical groups and, as consequence, of the ethnic identity, Barth influenced the rethinking of the ethnographical studies into an assimilationist perspective. Initially proposes a path in the direction for the comprehension of indigenous ethnic identity, in order to, discuss its influence and adoption by the Brazilian Law, particularly from the promulgation of the Federal Constitution/88. Considering these anthropological studies as references, the proposed investigation intends to reveal the understanding of the indigenous ethnic identity that emerges in cases from Federal Supreme court (STF) which decided issues related to the indigenous cause since the promulgation of Federal Constitution / 88. Among the decisions to be analyzed, it stands out the case of the demarcation of the of the indigenous land named Raposa Serra do Sol in the state of Roraima, judged by STF, through the Petition no. 3388, during 1998 and 1999. To be considered paradigmatic in the form how it faced the problems related to that demand and also for the controversial solutions which were proposed, that judgment brings questions in order to the limits of the indigenous ethnic identity. Finally, it proposes a review of the understanding over the ethnic identity adopted by the Justice of the Supreme Court, which seems not to break with culturalist conception, according to the national legislation, since the Federal Constitution/88 and by the ILOs Convention 169 (Decree no. 5051/2004), which had already changed such comprehension. It also analyses other decisions from the Federal Supreme Court related to cases which the indigenous ethnic identity is relevant to the debate of conflict solution, starting from several ones who were influenced by the decision taken in the case of the Pet no. 3388. A significant number of analyzed judgments are related to land property conflict and indigenous settlement. However, besides these, there are also analyzed judgments which are related to the competence and of Penal Imputability of the Indians. All of the cases have the comprehension of the indigenous ethnic identity and its consequences of recognition or not. The research is a juridical-sociological format, once it discusses the concrete accomplishment of the provisions from the Federal Constitution / 88 and their relations with other regulations from the Statute of the Indian (Law n. 6.001/73) and ILOs Convention 169 (Decree no. 5.051/2004). It follows the juridical-exploratory methodological type, through the analysis of the indigenous ethnic identity, its relation with the practice of the rights and its recognition by STF. It also adopts the juridical-proposal type, because it starts from the questioning of judicial rules their interpretation by STF and, then, it tries to propose a change in this understanding. According to the techniques of content analysis, it is a theoretical research, that it analyzes contents of legislative texts, jurisprudences and doctrinaire on the theme.